THE RELEVANCE OF THE PRINCIPLE OF GOOD FAITH TO THE LEGAL CERTAINTY OF MARRIAGE AGREEMENTS - Sabrina Fiddini Achmad; Mutiara Eldiena Fitri; Ida Ayu Intan Budha Ranny; Shafiyah Nur Azizah (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
This research was conducted to examine and analyze the importance of applying the principle of good faith in prenuptial agreements. This need arose due to existing weaknesses, whereby the parties to the agreement could act in bad faith, thereby misusing the agreement as a tool to protect their personal interests, which in turn could potentially harm third parties. In an effort to ensure legal certainty and examine the binding force of prenuptial agreements, the application of the principle of good faith is fundamental when drafting agreements. The application of this principle is expected to prevent future losses when prenuptial agreements are legalized and enforced. This study uses a legal research method with a theoretical research type and analyzes legal materials through a legislative approach, a conceptual approach, and case studies. The findings of this study indicate that the application of the principle of good faith in prenuptial agreements plays an important role as a preventive measure against the misuse of the objectives and goals of the agreement. The application of this principle aims not only to ensure legal certainty and protection for both parties, but also for third parties.